Extraction of Antioxidant Compounds from Sargassum sp. Using Water and Ultrasound Assisted Extraction Method as A Derivation of Green Chemistry Principles - Samantha Githa Ratna Sonia; Boy Arief Fachri; Bekti Palupi (JOBC, 2022)
The content of bioactive compounds in Sargassum sp. has already been used in various fields. The Ultrasound Assisted Extraction (UAE) method and water solvent have met the principles of green chemistry, so it is used in this study to extract antioxidant compounds contained in Sargassum sp. The principle of green chemistry primarily aims to reduce or eliminate the impact of environmental damage. This research was conducted with several process variables, including the ratio of the sample mass to the volume of solvent (0.05 – 0.15 g/mL), time (30 – 40 minutes), and power (170 – 180 W) using the UAE method and water solvent (Aquadest) on the total phenol value of Sargassum sp. Analysis of variance was carried out with the help of Design Expert software, Response Surface Method - Central Composite Design, to determine the effect of the process variables carried out in the extraction process on the total phenol yield. The analysis of variance in this study shows the suitability between the research design and the study results, which is indicated by an R2 value of 0.9785. The highest results were obtained with a variable ratio of sample mass to solvent volume of 0.18 (g/mL), time of 40 minutes, and power of 180 W, with a total phenol yield of 212.8 mg GAE/g and antioxidant activity of 12.3%.